2003
DOI: 10.2466/pr0.2003.93.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Backchannel Utterances on Facilitating Idea-Generation in Japanese Think-Aloud Tasks

Abstract: The relation between backchannel utterance and idea-generation has hardly been studied. Based on preliminary investigations, we formulated a hypothesis that a listener's backchannel utterances facilitate a speaker's idea-generation. This study experimentally manipulated the frequency of backchannel utterances by listeners during speakers' idea-generation for think-aloud tasks. 16 Japanese female undergraduates participated. Analysis indicated that frequent backchannel utterances increased not only the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Through the fact that the interaction was found only in idea-generation, it was suggested that backchannel utterances had two influencing pathways; one was facilitating positive social cognition and motivation which led to speaking more, and the other was activating idea-generation itself. support for idea-generation, thinking, backchannel utterance, copresence, communication (1) et al 2003et al Matarazzo et al 1964 Matarazzo et al Finke, Ward, & Smith 1992 2 (1)…”
mentioning
confidence: 99%
“…Through the fact that the interaction was found only in idea-generation, it was suggested that backchannel utterances had two influencing pathways; one was facilitating positive social cognition and motivation which led to speaking more, and the other was activating idea-generation itself. support for idea-generation, thinking, backchannel utterance, copresence, communication (1) et al 2003et al Matarazzo et al 1964 Matarazzo et al Finke, Ward, & Smith 1992 2 (1)…”
mentioning
confidence: 99%